Analisis Trade-Off Risiko dan Return pada Investasi Modern - Febrina Friska; Anggun Feby Ivana Putri; Dini Anggraini; Anisa Siti Nurjanah; Mukhtaruddin (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
This research was conducted to provide a comprehensive understanding of the relationship between risk and return in the investment decision-making process in the modern financial era, which is characterized by technological advancements, market digitalization, and changes in investor behavior. A qualitative approach with a literature study method was used to examine fundamental theories such as Modern Portfolio Theory (MPT) and the Capital Asset Pricing Model (CAPM), as well as to review contemporary research findings related to current financial market dynamics. Through an in-depth analysis of various academic sources, this study found that although the basic principle of a positive relationship between risk and return remains a mainstay in financial science, in reality, this relationship is becoming increasingly complex due to high market volatility, the rapid spread of information, and the emergence of diverse digital investment instruments and platforms. Technological developments such as artificial intelligence, big data analytics, and automated investment systems (robo-advisors) are also changing the way investors evaluate risk and develop portfolio strategies. The ability of technology to provide real-time data and predictive analysis offers opportunities for investors to conduct risk assessments more accurately and responsively. On the other hand, the emergence of phenomena such as herd behavior, fear of missing out (FOMO), and other psychological biases adds a layer of complexity in understanding the relationship between risk and return in modern investments. Overall, this study affirms that achieving optimal and sustainable investment decisions requires an integration of understanding classical theory, the ability to adapt to changes in market behavior, and the utilization of advanced financial technology. Therefore, the results of this study are expected to serve as a reference for academics and practitioners in formulating more effective investment strategies amid the increasingly fast and uncertain dynamics of the global market.